Vitamin D levels in systematic lupus erythematosus patients: association with disease activity index and interferon alpha - Enteshari-moghaddam, Afsaneh; Ravaei, Gholamreza; Azami, Ahad (International Journal of Basic & Clinical Pharmacology, 2018)
Background: In different studies the correlation between systemic lupus erythematosus (SLE) and disease activity with vitamin D has been shown. The role of different interferons especially interferon alpha (IFN-α) in lupus pathogenesis have been previously shown. Considering the role of vitamin D and IFN-α, it is possible that these two could demonstrate the SLE activity. This study aimed to investigate the association between vitamin D levels and IFN-α with disease activity index in Ardabil city SLE patients. Methods: In this case control study, 50 SLE patients and 50 age and sex matched healthy subjects were recruited. Patients had serum 25-OH Vitamin D concentration and disease activity recorded. Vitamin D and IFN-α levels were compared between two groups and also, levels of anti-dsDNA, and SLEDAI in case group was measured. Statistical methods were used to determine the correlation between vitamin D and IFN-α with disease activity index at baseline. Results: Vitamin D deficiency (<40 nmol/L) was detected in 20% of SLE patients. Vitamin D level in case group significantly lower than control group (23.94±11.93 vs. 29.10±11.40 ng/ml, p=0.02). The IFN-α amount in case group significantly upper than control group (396.60±54.73 vs. 200.38±14.42, p=0.001). There was significantly negative correlation between vitamin D with IFN-α (r=-0.413, p=0.003), SLEDAI (r=-0.492, p<0.001) and anti-dsDNA (r=-0.417, p=0.003). There was positive correlation between IFN-α with SLEDAI (r=0.358, p=0.01) and anti-dsDNA (p=0.297, p=0.03). Conclusions: Results showed that the low vitamin D was associated with a higher disease activity in SLE patients. Also, it seems that, the improvement of vitamin D levels by decreasing IFN-α could help in controlling disease activity in future.